2021
DOI: 10.1111/ics.12698
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level red plus near infrared lights combination induces expressions of collagen and elastin in human skin in vitro

Abstract: Objective Light therapy has attracted medical interests as a safe, alternative treatment for photo‐ageing and photo‐damaged skin. Recent research suggested the therapeutic activity of red and infrared (IR) lights may be effective at much lower energy levels than those used clinically. This study was to evaluate the efficacy of low‐level red plus near IR light emitting diode (LED) combination on collagen and elastin and ATP production. Methods Human dermal fibroblasts or skin tissues were irradiated daily by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This was consistent with Opel's finding [7] showed that the 630-700 nm red light has a beneficial effect on skin rejuvenation. This is consistent with the reports by Kim et al [9] and Lee et al [10], and the 640 nm red light combined with lowintensity IR light 830 nm was found to be effective in treating photo-aged skin [11]. Papageorgiou et al [12] presented a combination of 415 nm blue light and 633 nm red light to improve the efficacy of acne treatment of 24 patients with mild to moderate facial acne.…”
Section: Introductionsupporting
confidence: 86%
“…This was consistent with Opel's finding [7] showed that the 630-700 nm red light has a beneficial effect on skin rejuvenation. This is consistent with the reports by Kim et al [9] and Lee et al [10], and the 640 nm red light combined with lowintensity IR light 830 nm was found to be effective in treating photo-aged skin [11]. Papageorgiou et al [12] presented a combination of 415 nm blue light and 633 nm red light to improve the efficacy of acne treatment of 24 patients with mild to moderate facial acne.…”
Section: Introductionsupporting
confidence: 86%
“…For example, it could be that the strong dose of brief periods of low-level red-light therapy is producing irreversible damage at the cellular level to the structure and physiology of the posterior eye components involved in signaling eye growth. Red light stimulation has been shown to increase mRNA expression and production of several types of collagen in different cell types 80,81 . This increase in the production of collagen may contribute to the changes in ocular structure observed in low-level red-light subjects.…”
Section: Background: the Value Of Lightmentioning
confidence: 97%
“…Red light stimulation has been shown to increase mRNA expression and production of several types of collagen in different cell types. 80,81 This increase in the production of collagen may contribute to the changes in ocular structure observed in low-level red-light subjects. It must be noted that all these possibilities are merely speculations at this point.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In particular, the impact of 5G electromagnetic radiation (EMR) on human skin has been drawing attention [ 4 , 5 , 6 ], since the skin interfaces between the body and the external environment and serves as the primary target tissue for EMR from the environment. Indeed, the EMR such as ultraviolet, visible light like blue light and infrared radiation affect the skin physiology significantly [ 7 , 8 , 9 , 10 ], signifying that 5G EMR may also have effects on the skin. Also, it is highly probable that the skin may be the primary target tissue of 5G EMR since 28 GHz EMR from the environment cannot penetrate into our body deeper than 2 mm [ 11 ].…”
Section: Introductionmentioning
confidence: 99%